1968
DOI: 10.1172/jci105941
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a short-term fast on albumin synthesis studied in vivo, in the perfused liver, and on amino acid incorporation by hepatic microsomes

Abstract: AB S TRA CT Carbonate-14C was used to label the hepatic intracellular arginine pool and direct measurement of albumin synthesis was made in six rabbits before and after an 18-36 hr fast. 18 perfusion studies were performed with livers derived from fed and fasted rabbits (18-24 hr). Microsomal amino acid-incorporating ability with leucine-MH and phenylalanine-14C was compared in 17 studies, using microsomes isolated from livers taken from fed and fasted rabbits and from isolated perfused livers whose donors wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0

Year Published

1969
1969
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(38 citation statements)
references
References 31 publications
6
32
0
Order By: Relevance
“…The product, prealbumin, is in turn cleaved in the Golgi vesicles to produce the secreted form of albumin. It is known that fasting or feeding a lowprotein diet rapidly induces a sharp decrease in albumin production in both humans (20,21) and rats (22). The present study also showed that plasma albumin concentration was decreased in the malnourished rats fed a low-protein diet (Table 3).…”
Section: Discussionsupporting
confidence: 76%
“…The product, prealbumin, is in turn cleaved in the Golgi vesicles to produce the secreted form of albumin. It is known that fasting or feeding a lowprotein diet rapidly induces a sharp decrease in albumin production in both humans (20,21) and rats (22). The present study also showed that plasma albumin concentration was decreased in the malnourished rats fed a low-protein diet (Table 3).…”
Section: Discussionsupporting
confidence: 76%
“…However, it is assumed that the rate of urea synthesis remains unchanged during the 24 hr interval. Studies in fasted and fed animals whose individual rates of urea synthesis varied from 200 to 450%/day have shown that these fractional rates determined by endogenous and exogenous urea-24C specific activity curves agree very well (14). In one patient in this study where it was possible to determine the fractional rates by the two methods, the agreement was nearly perfect.…”
Section: Discussionsupporting
confidence: 53%
“…Further, the 1'C label must, as nearly as possible, act as a pulse label so that the liver is rapidly freed of labeled precursor permitting the fall in plasma specific activity after distribution to reflect the continued synthesis of cold urea. Evidence to support these assumptions inherent in the method has been presented and reviewed previously (14,(24)(25)(26)(27). McFarlane (11) has shown that in the human the curves of endogenously produced urea-14C and exogenously administered urea-'3C are different reflecting the continued labeling of urea and protein within the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The technique for the rabbit liver perfusion has been described in detail (6). Briefly, under light ether anesthesia, the portal vein was cannulated and perfusion started immediately from a reservoir.…”
Section: Methodsmentioning
confidence: 99%
“…DISCUSSION To our knowledge, this is the first time that the isolated, perfused rabbit liver has been employed in studies of bile acid synthesis. An identical preparation had been employed previously in studies of albumin synthesis and had been considered suitable for this purpose by currently accepted standards (6). In the present experiments, a number of-additional criteria (glycocholate production and incorporation of 14C from labeled precursors) were used to establish that this preparation is suitable for studies of de novo bile-acid synthesis.…”
Section: Gas-liqutid Chromatography (Glc)mentioning
confidence: 99%